Pareshan Hona Choriye Aur Jeena Seekhiye - Carnegie, Dale (Lahore Sheikh Muhammad Bashir And Sons)
A "plan for stopping worry at its source. [The author] shows, in down-to-earth, specific terms, how to turn the destructive frustration of worry into creative paths, whether that worry is caused by job, money, family of a combination of problems. Each point is illustrated with ... anecdotes and the experiences of actual people who have mastered worry."
Keywords: Conduct of life